2018
DOI: 10.1073/pnas.1812055115
|View full text |Cite
|
Sign up to set email alerts
|

Dengue type 1 viruses circulating in humans are highly infectious and poorly neutralized by human antibodies

Abstract: The four dengue virus (DENV) serotypes are mosquito-borne flaviviruses of humans. The interactions between DENVs and the human host that lead to asymptomatic, mild, or severe disease are poorly understood, in part, because laboratory models are poor surrogates for human DENV disease. Virologists are interested in how the properties of DENVs replicating in people compare with virions propagated on laboratory cell lines, which are widely used for research and vaccine development. Using clinical samples from a DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
98
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(108 citation statements)
references
References 30 publications
10
98
0
Order By: Relevance
“…Therefore, the detection of DENV within the biopsy tissue suggests that a persistent infection was established prior to immune suppression and that this infection did not arise from later therapeutic attempts. 29 Together, the observations from our patient and other flaviviruses suggest that virus within the host may be resistant to immune pressures and that the CNS may be an underappreciated anatomical reservoir for flaviviruses. For example, West Nile virus has been detected intermittently in urine up to 6 years postinfection in patients with previous West Nile virus encephalitis.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, the detection of DENV within the biopsy tissue suggests that a persistent infection was established prior to immune suppression and that this infection did not arise from later therapeutic attempts. 29 Together, the observations from our patient and other flaviviruses suggest that virus within the host may be resistant to immune pressures and that the CNS may be an underappreciated anatomical reservoir for flaviviruses. For example, West Nile virus has been detected intermittently in urine up to 6 years postinfection in patients with previous West Nile virus encephalitis.…”
Section: Discussionmentioning
confidence: 59%
“…However, it is noted that ZIKV RVPs are made in defined cell types (typically BHK cells), and there is evidence suggesting that some flavivirus properties, particularly maturity, can be influenced by the producing cell type (whether live virus or RVP) (47).…”
Section: Discussionmentioning
confidence: 99%
“…Maturation of flaviviruses occurs by the cleavage of the prM protein to M (9), but this is generally incomplete, with virus maturity (whether live virus or RVP) (Cherrier 2009; ref for ZIKV) being influenced by the producing cell type (Dejninarattisai et al, 2015). In addition, patient-derived DENV showed higher levels of maturity compared with the same virus following passage in cells (47,48). The maturation state of flaviviruses is thought to be important for infectivity and for neutralization by sera in clinical studies.…”
Section: Generation Of Zikv Rvps With Distinct Maturation Statesmentioning
confidence: 99%
“…However, the suboptimal efficacy and safety profile of a recently licensed DENV vaccine has been partly attributed to its inability to generate a balanced neutralizing antibody response to all four serotypes (Hadinegoro et al, 2015). Additionally, there may be important antigenic differences between circulating and lab-adapted strains (Lim et al, 2019;Raut et al, 2019), as well as among strains even within a given serotype (Bell, Katzelnick, & Bedford, 2019;Katzelnick et al, 2015). Antigenic mismatch between vaccine and circulating strains impacted vaccine efficacy (Juraska et al, 2018), highlighting the importance of rational selection of vaccine components.…”
Section: Introductionmentioning
confidence: 99%
“…J9 and J8 also potently neutralized contemporary DENV1-4 isolates with IC50 values < 50 ng/ml ( Figure S3). Additionally, in contrast to C4 and the crossreactive DII fusion loop-specific mouse mAb E60 (Goo, VanBlargan, Dowd, Diamond, & Pierson, 2017;Nelson et al, 2008;Oliphant et al, 2006), but similar to EDE bNAbs (Dejnirattisai et al, 2015), J9 and J8 potently neutralized DENV regardless of virion maturation state ( Figure S4), which can indirectly modulate epitope exposure (Cherrier et al, 2009;Goo et al, 2019;Nelson et al, 2008) and has been shown to be distinct among circulating versus labadapted strains (Raut et al, 2019). We also tested the ability of mAbs to mediate neutralization after virus attachment to cells, which is characteristic of many potently neutralizing antibodies against flaviviruses (Goo et al, 2019;Nybakken et al, 2005;Sukupolvi-Petty et al, 2010;Vogt et al, 2009;Xu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%